Crosstalk Between Mammalian Autophagy and the Ubiquitin-Proteasome System - Kocaturk, Nur Mehpare; Gozuacik, Devrim (Frontiers in Cell and Developmental Biology, 2018)
Crosstalk Between Mammalian Autophagy and the Ubiquitin-Proteasome System Nur Mehpare Kocaturk1 and Devrim Gozuacik1,2,3* 1Sabanci University, Faculty of Engineering and Natural Sciences, Molecular Biology, Genetics and Bioengineering Program, Istanbul, 34956, Turkey. 2Sabanci University, Center of Excellence for Functional Surfaces and Interfaces for Nano Diagnostics (EFSUN), Istanbul, 34956, Turkey. 3Sabanci University Nanotechnology and Application Center (SUNUM), Istanbul, 34956, Turkey. * Correspondence: Devrim Gozuacik dgozuacik@sabanciuniv.edu Autophagy and the ubiquitin–proteasome system (UPS) are the two major intracellular quality control and recycling mechanisms that are responsible for cellular homeostasis in eukaryotes. Ubiquitylation is utilized as a degradation signal by both systems, yet, different mechanisms are in play. The UPS is responsible for the degradation of short-lived proteins and soluble misfolded proteins whereas autophagy eliminates long-lived proteins, insoluble protein aggregates and even whole organelles (e.g., mitochondria, peroxisomes) and intracellular parasites (e.g., bacteria). Both the UPS and selective autophagy recognize their targets through their ubiquitin tags. In addition to an indirect connection between the two systems through ubiquitylated proteins, recent data indicate the presence of connections and reciprocal regulation mechanisms between these degradation pathways. In this review, we summarize these direct and indirect interactions and crosstalks between autophagy and the UPS, and their implications for cellular stress responses and homeostasis.